Addressing Marine and Coastal Governance Conflicts at the Interface of Multiple Sectors and Jurisdictions - Bellanger, Manuel; Speir, Cameron; Blanchard, Fabian; Brooks, Kate; Butler, James R. A.; Crosson, Scott; Fonner, Robert; Gourguet, Sophie; Holland, Daniel S.; Kuikka, Sakari; Le Gallic, Bertrand; Lent, Rebecca; et al. (Frontiers in Marine Science, 2020)
Marine and coastal activities are closely interrelated, and conflicts among different sectors can undermine management and conservation objectives. Governance systems for fisheries, power generation, irrigation, aquaculture, marine biodiversity conservation, and other coastal and maritime activities are typically organized to manage conflicts within sectors, rather than across them. Based on the discussions around eight case studies presented at a workshop held in Brest in June 2019, this paper explores institutional approaches to move beyond managing conflicts within a sector. We primarily focus on cases where the groups and sectors involved are heterogeneous in terms of: the jurisdiction they fall under; their objectives; and the way they value ecosystem services. The paper first presents a synthesis of frameworks for understanding and managing cross-sectoral governance conflicts, drawing from social and natural sciences. We highlight commonalities but also conceptual differences across disciplines to address these issues. We then propose a novel analytical framework which we used to evaluate the eight case studies. Based on the main lessons learned from case studies, we then discuss the feasibility and key determinants of stakeholder collaboration as well as compensation and incentive schemes. The discussion concludes with future research needs to support policy development and inform integrated institutional regimes that consider the diversity of stakeholder interests and the potential benefits of cross-sectoral coordination.